2016
DOI: 10.3109/08958378.2015.1130758
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of a prototype e-cigaret device and three flavor formulations: a 90-day inhalation study in rats

Abstract: A prototype electronic cigaret device and three formulations were evaluated in a 90-day rat inhalation study followed by a 42-day recovery period. Animals were randomly assigned to groups for exposure to low-, mid- and high-dose levels of aerosols composed of vehicle (glycerin and propylene glycol mixture); vehicle and 2.0% nicotine; or vehicle, 2.0% nicotine and flavor mixture. Daily targeted aerosol total particulate matter (TPM) doses of 3.2, 9.6 and 32.0 mg/kg/day were achieved by exposure to 1 mg/L aeroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 37 publications
(41 reference statements)
4
41
4
2
Order By: Relevance
“…Electronic nicotine delivery systems or e-cigarettes (e-Cigs) have become the sought-after product partly due to the belief that they are much safer than traditional cigarettes. Preclinical studies have shown that nicotine (the principal ingredient of e-liquid) can cause OS, exacerbation of cerebral ischemia and secondary brain injury [11, 34, 41]. Likewise, chronic e-Cig vaping could be prodromal to cerebrovascular impairment and promote cerebrovascular conditions similar to that associated with chronic TS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic nicotine delivery systems or e-cigarettes (e-Cigs) have become the sought-after product partly due to the belief that they are much safer than traditional cigarettes. Preclinical studies have shown that nicotine (the principal ingredient of e-liquid) can cause OS, exacerbation of cerebral ischemia and secondary brain injury [11, 34, 41]. Likewise, chronic e-Cig vaping could be prodromal to cerebrovascular impairment and promote cerebrovascular conditions similar to that associated with chronic TS.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models and different protocols have been used for preclinical research. This includes, transdermal implantation of osmotic mini pump [6, 8], IV injection of nicotine/tobacco extract solution [9, 10], direct inhalation of TS in animal restraint device [11]. Most of these exposure conditions fail to simulate realistic smoking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Using a different cell culture model for cytotoxicity that assesses vapors from e-liquids (volatility of the liquid, not the aerosols emitted from an e-cig), cinnamon-flavorings had the most cytotoxicity among 36 different e-liquids and confirmed among sources from multiple manufacturers; the constituents in the cinnamon-flavored liquids thought to be responsible for the cytotoxicity were cinnamaldehyde (CAD) and 2-methoxycinnamaldehyde (2MOCA) (235, 236). In vivo, o ne study reported no effect in rats, but they chose a mixture of flavors with constituents not known to cause cell damage or inflammation (237). Menthol is a flavor of concern for enhancing the abuse liability in cigarettes (238).…”
Section: Introductionmentioning
confidence: 99%
“…Werley et al exposed rats to low-dose, mid-dose, and high-dose aerosols from e-cigarette formulations for 90 days. 20 There was a dose-dependent increase in bronchoalveolar lavage fluid lactate dehydrogenase levels, total protein levels, the number of alveolar macrophages, the number of neutrophils, and lung weight at 90 days. This effect was largely explained by the vehicle control (a mixture of glycerin and propylene glycol) and resolved after a 42 days washout period.…”
Section: E-cigarette Effects In Animal Modelsmentioning
confidence: 91%